Boudon's Interpretation of Durkheim Sociology. Issue 1 (1st December 2020) - Leroux, Robert
Abstract: It is well known that Durkheim was a major source of influence in most of Boudon's writings. But his vision of Durkheim has evolved a lot over the years. In the 1960s until the 1990s, he presented Durkheim as a positivist, fairly close to Auguste Comte, and he considered The Rules of the Sociological Method as a mediating work which announced all of the Durkheim's thought. In his most recent works, Boudon brings an original perspective that Durkheim was an important theorist of rationality. Résumé: Boudon a développé une admiration durable pour Durkheim dont il ne s'est jamais départi. Durkheim n'a jamais cessé en effet d'être pour lui un inspirateur, mais la lecture qu'il en fait a néanmoins évolué au fil du temps. Des années 1960 aux années 1990 il le présente comme un auteur positiviste dont il admire la réflexion sur la scientificité de la sociologie. Après 1990 il le présente comme un précurseur malgré lui de l'individualisme méthodologique, et traduit sa sociologie dans le langage de la théorie de l'action.